"Small Miracles" --Behavioral Insights to Improve Development Policy - Demeritt, Allison; Hoff, Karla (World Bank Group, Washington, DC, 2015)
One of the most fruitful advances in modern economics has been the introduction of psychological realism into the model of "economic man." The World Development Report 2015 organizes the evidence about how humans actually think and make decisions into a coherent framework useful for designing development policy. This paper elaborates on the three principles of human thinking that constitute the report's intellectual framework: Human thinking is dual process -- automatic as well as deliberative (thinking automatically); it is conditioned by social context and the salience of social identities (thinking socially); and it is shaped by mental models that are socially constructed (thinking with mental models). Behavioral insights create scope for policy interventions that produce "miracles" from the perspective of traditional economics.